Preparation method and application of cellulose-based hydrogel with dual temperature response

The composite cellulose-based hydrogel (Gel-H/C gel) prepared by one pot method uses CMC to adjust the UCST and LCST temperature, which solves the problem of excessive phase transition temperature of cellulose-based gel and achieves double-layer Temperature response and excellent mechanical properties, suitable for smart windows and information encryption devices.

CN119431672AActive Publication Date: 2025-02-14NANJING FORESTRY UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411696748.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-14
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

Cellulose-based gel systems have a widespread problem of excessive phase transition temperature of minimum co-soluble temperature (LCST), which limits their wide application.

Method used

A composite cellulose-based hydrogel (Gel-H/C gel) was prepared by one pot method by using polyacrylamide (PAM), hydroxypropyl cellulose (HPC), and sodium carboxymethyl cellulose (CMC) ) as raw material, and the maximum co-soluble temperature (UCST) and LCST temperature of the hydrogel are adjusted by different concentrations of CMC solutions to achieve dual temperature response.

Benefits of technology

Two-stage transparency switching is achieved in the range of 1-50°C, which improves the mechanical properties and freezing resistance of the hydrogel. It is suitable for smart windows and information encryption devices, showing excellent thermal insulation performance and information security.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431672A_ABST
    Figure CN119431672A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of cellulose-based hydrogel with dual temperature response. The cellulose-based hydrogel with dual temperature response is prepared through a one-pot method, the synthetic route is simple, and the reaction conditions are mild. By adjusting the concentration of sodium carboxymethyl cellulose (CMC) in the system, the hydrogel has an adjustable highest consolute temperature (5-20 DEG C) and an adjustable lowest consolute temperature (30-50 DEG C), so that the mechanical property and the anti-freezing property of the hydrogel are improved. The gel can also realize reversible transparency switching along with the change of ambient temperature, so that the gel can be used for preparing hydrogel intelligent windows and information encryption equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer materials, and in particular relates to a preparation method of a cellulose-based hydrogel (hereinafter referred to as Gel-H / C gel) with dual temperature response, and a product and application thereof. Background Art

[0002] Hydrogels have unique three-dimensional network structures and high water content, and have the advantages of stretchability, high transmittance and biocompatibility. Among them, phase change hydrogel is a smart material that can respond to environmental changes. When subjected to external stimuli (such as heat, pH, electricity, salt, solvents, etc.), dynamic hydrogen bonds, hydrophobic interactions or ionic interactions can be used to change the aggregation state of macromolecules and change their transmittance, thereby achieving a reversible change in transparency. Phase change hydrogels not only have many advantages of traditional hydrogels, but also have the advantages of controllable phase change temperature, simple preparation process and low cost compared to traditional phase change materials. Therefore, this unique response mechanism has made phase change hydrogels widely concerned in the fields of smart windows, patterned information encryption, motion monitoring and medical devices.

[0003] Cellulose is one of the most abundant natural polymers on earth, with many advantages such as high mechanical strength, renewability, biocompatibility and biodegradability. Its derivatives such as methylcellulose (MC), hydroxypropylcellulose (HPC) and hydroxypropylmethylcellulose (HPMC) exhibit minimum co-solubility temperature (LCST) characteristics due to hydrophobic aggregation in aqueous solution at high temperatures. However, cellulose-based gel systems generally have the problem of too high LCST phase transition temperature, which limits their wide application.

[0004] Sodium carboxymethyl cellulose (CMC) is a macromolecular anionic sodium salt with excellent hydrophilicity. In addition, CMC also has a large number of hydroxyl and carboxyl groups, which can form entanglements with the polymer molecular chains in the hydrogel, improve the light transmittance and mechanical properties of the hydrogel, and overcome the problem of loss of inorganic salt solutions during long-term use of the hydrogel. After CMC is introduced into the thermochromic hydrogel system, it can not only + The strong hydration of ions affects the hydrogen bonds in the gel system, thus achieving the regulation of the phase transition temperature. At the same time, the CMC macromolecular chains and the hydrogel matrix are cross-linked through hydrogen bonds, which can enhance the mechanical properties of the composite material and prevent volume shrinkage caused by phase change.

[0005] This patent uses polyacrylamide (PAM), HPC and CMC as raw materials, and adopts a one-pot strategy to prepare a composite cellulose-based hydrogel (Gel-H / C gel). The maximum eutectic temperature (UCST) and LCST temperature of the hydrogel can be flexibly adjusted by using CMC solutions of different concentrations, and two-level transparency switching is achieved in the range of 1-50°C. In addition, the thermochromic smart window prepared by sandwiching the Gel-H / C gel between two glass plates has excellent visible light transmittance and solar modulation ability. In outdoor tests, the hydrogel smart window showed excellent thermal insulation performance. Compared with ordinary windows, the maximum cooling effect was about 3.4°C, while achieving energy saving, lighting and privacy protection requirements. In addition, using the difference in temperature responsiveness of hydrogels with different CMC contents, an information encryption device was designed, which can realize dual encryption of QR code and pattern information, showing its good application prospects in the field of information encryption. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] As one aspect of the present invention, the present invention provides a method for preparing a dual temperature-responsive cellulose-based hydrogel, which comprises the following steps:

[0008] First, hydroxypropyl cellulose (HPC) and acrylamide (AM) were dissolved in deionized water; then, appropriate amounts of sodium carboxymethyl cellulose (CMC), crosslinker N,N'-methylenebisacrylamide (MBA) and initiator ammonium persulfate (APS) were added, stirred until completely dissolved and centrifuged to remove bubbles; finally, the prepared precursor solution was injected into the mold, sealed and reacted at high temperature to obtain the final dual temperature-responsive cellulose-based hydrogel Gel-H / C. The hydrogels obtained by adding different concentrations of CMC are recorded as Gel-H / Cx, where x is the mass percentage concentration of CMC.

[0009] As a preferred embodiment of the method for preparing a dual temperature-responsive cellulose-based hydrogel described in the present invention, hydroxypropyl cellulose (HPC) and acrylamide (AM) are dissolved in deionized water, wherein the concentration of hydroxypropyl cellulose (HPC) is 5 wt % and the concentration of acrylamide (AM) is 2 mol / L.

[0010] As a preferred scheme of the method for preparing a dual temperature-responsive cellulose-based hydrogel described in the present invention: the prepared precursor solution is injected into a sealed mold and reacted at a high temperature to obtain the final dual temperature-responsive cellulose-based hydrogel Gel-H / C, the reaction temperature is 60°C, and the reaction time is 6 hours.

[0011] As another aspect of the present invention, the present invention also provides the use of the dual temperature-responsive cellulose-based hydrogel in thermochromic smart windows.

[0012] As another aspect of the present invention, the present invention also provides the use of the dual temperature-responsive cellulose-based hydrogel in anti-counterfeiting materials.

[0013] Beneficial effects of the present invention: A cellulose-based hydrogel (Gel-H / C gel) with dual temperature response is prepared by a one-pot method. The dynamic hydrogen bond changes between PAM, HPC and water molecules and the hydrophobic aggregation characteristics of HPC make the Gel-H / C hydrogel have UCST and LCST phase transition behaviors. + Ions can change the hydrogen bonding interactions between polymers through ion-dipole interactions and strong hydration, and entangle with polymer chains, so that Gel-H / C gel has adjustable UCST (5-20℃) and LCST (30-50℃) transition temperatures, improving mechanical properties and antifreeze properties. Gel-H / C gel smart windows can achieve reversible switching of transparency with changes in ambient temperature, ensuring daytime lighting, nighttime privacy protection and excellent thermal insulation performance. In addition, Gel-H / C gel can be used as an encryption, decryption and re-encryption device to encrypt or decrypt at different temperatures, which greatly improves the security and mobility of information. This work provides new ideas for the preparation of hydrogel smart windows and information encryption devices through phase separation mechanisms, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0015] Figure 1 This is a flow chart of a cellulose-based hydrogel (Gel-H / C gel) with dual temperature response prepared in Example 1.

[0016] Figure 2(a) ATR-FTIR spectra of different Gel-H / C hydrogels. (b) Variable temperature FTIR spectra of Gel-H / C5 hydrogel in the temperature range of 2℃-40℃. (c) Schematic diagram of the phase transition mechanism of Gel-H / C hydrogel.

[0017] Figure 3 (a) CLSM images of Gel-H / C5 hydrogel at different temperatures. (b) SEM images of Gel-H / C5 hydrogel at different temperatures. (c) SAXS scattering intensity diagram of Gel-H / C5 hydrogel at 2℃, 25℃ and 40℃. (d) Comparison of the maximum tensile strength and strain of Gel-H / C hydrogel. (e) DSC curve of Gel-H / C hydrogel.

[0018] Figure 4 This is the tensile strength curve of Gel-H / C gel with different CMC contents.

[0019] Figure 5 Images of the distortion and stretching of Gel-H / C gel before and after freezing at -15°C.

[0020] Figure 6 is the transmittance of Gel-H / C gel at different temperatures in the range of 250-2500nm.

[0021] Figure 7 Comparison between smart windows made of Gel-H / C gel and ordinary windows made of glass in a simulated house model.

[0022] Figure 8 (a) Information encryption, thermal decryption, and self-encryption process using the Gel-H / C hydrogel two-dimensional code information encryption device; and (b) Information thermal encryption and erasure process using the Gel-H / C hydrogel patterned information encryption device. DETAILED DESCRIPTION

[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0024] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0025] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0026] Example 1 Preparation method of a dual temperature-responsive cellulose-based hydrogel (Gel-H / C gel)

[0027] Example 2 Effect of different CMC contents on the structure of Gel-H / C hydrogel

[0028] Example 3 Changes in the microstructure of Gel-H / C5 hydrogel during phase transition

[0029] Example 4 Thermal insulation performance test of Gel-H / C gel at different temperatures

[0030] Example 5 Dual thermal response capability and controllable dynamic visual changes based on Gel-H / C gel

[0031] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0032] Example 1

[0033] Preparation method of dual temperature-responsive cellulose-based hydrogel (Gel-H / C gel)

[0034] First, hydroxypropyl cellulose (HPC) and acrylamide (AM) are dissolved in deionized water; then, appropriate amounts of sodium carboxymethyl cellulose CMC, crosslinking agent N,N'-methylenebisacrylamide (MBA) and initiator ammonium persulfate (APS) are added, stirred until completely dissolved and then centrifuged to remove bubbles; finally, the prepared precursor solution is injected into the mold, sealed and reacted at high temperature to obtain the final dual temperature-responsive cellulose-based hydrogel Gel-H / C. The hydrogels obtained by adding different concentrations of CMC are recorded as Gel-H / Cx, where x is the mass percentage concentration of CMC. The specific preparation process is shown in the attached Figure 1 .

[0035] As a preferred embodiment of the method for preparing a dual temperature-responsive cellulose-based hydrogel described in the present invention, hydroxypropyl cellulose (HPC) and acrylamide (AM) are dissolved in deionized water, wherein the concentration of hydroxypropyl cellulose (HPC) is 5 wt % and the concentration of acrylamide (AM) is 2 mol / L.

[0036] As a preferred scheme of the method for preparing a dual temperature-responsive cellulose-based hydrogel described in the present invention: the prepared precursor solution is injected into a sealed mold and reacted at a high temperature to obtain the final dual temperature-responsive cellulose-based hydrogel Gel-H / C, the reaction temperature is 60°C, and the reaction time is 6 hours.

[0037] Example 2

[0038] Effects of different CMC contents on the structure of Gel-H / C hydrogel

[0039] In order to study the effect of different CMC contents on the structure of Gel-H / C hydrogels, attenuated total reflectance infrared spectroscopy (ATR-FTIR) and variable temperature infrared spectroscopy were performed. Figure 2 It can be seen from a that when the CMC concentration increases from 0 to 5wt%, the NH stretching vibration peak, C=O stretching vibration peak and -NH2 bending peak of the amide in the hydrogel all undergo red shifts, indicating that a stable strong hydrogen bond interaction is formed between CMC and the PAM molecular chain. In addition, the OH stretching vibration peak corresponding to the hydrogen bond undergoes a blue shift (from 3376cm -1 To 3405cm -1 ), this is because the free Na in CMC + It has strong hydration, which weakens the hydrogen bonds between cellulose molecules. Taking Gel-H / C5 hydrogel as an example, variable temperature infrared spectroscopy was performed at 2-50℃ to examine the structural changes during the phase transition, reflecting the internal hydrogen bond interactions of the gel before and after the UCST and LCST phase transitions. Figure 2 As can be seen in b, the OH stretching vibration peak shifts toward higher wavelengths as the temperature increases (from 3346 cm -1 Move to 3367cm -1 At the same time, the CO stretching vibration peak from HPC is significantly enhanced and increases from 1060 cm -1 Move to 1076cm -1 , indicating that the hydrogen bonds on the HPC molecular chains are weakened. Therefore, it can be inferred that the Gel-H / C5 hydrogel undergoes three states of structural changes as the temperature increases (see Appendix Figure 2 c). First, the Na of CMC + The hydrogen bonds between HPC and PAM molecular chains are weakened by ion-dipole interactions with the hydroxyl groups on the HPC chains. Instead, hydrogen bonds are gradually formed between HPC and water molecules. When the temperature continues to rise, Na +The strong hydration weakens the hydrogen bonds between HPC and water molecules, making HPC more prone to hydrophobic aggregation. In addition, as the temperature increases, the stretching vibration peaks of N-H, C=O, and -NH2 from PAM also shift towards higher wavenumbers, indicating that the hydrogen bonds between HPC and the PAM molecular chains are gradually dissociated as the temperature rises. Therefore, these results suggest that the UCST and LCST phase transition processes of the hydrogel are mainly caused by temperature-induced changes in hydrogen bonds, and the addition of CMC simultaneously leads to a decrease in the UCST and LCST phase transition temperatures of Gel-H / C5.

[0040] Example 3

[0041] Changes in the microstructure of Gel-H / C5 hydrogel during phase transition

[0042] The changes in the microstructure of Gel-H / C5 hydrogel during phase transition were further investigated by confocal laser scanning microscopy (CLSM). Attached Figure 3 In the CLSM image of a, the blue fluorescence represents the polymer-rich phase, which has refractive and scattering modulation on light. Therefore, the denser the blue area, the more opaque the hydrogel appears optically. At 25 °C (UCST < T < LCST), only a few bright spots were observed in the CLSM image of Gel-H / C5 hydrogel, indicating the lack of obvious light scattering domains at this time, so the hydrogel was in a transparent state. However, when the hydrogel was exposed to low temperature (2 °C, T < UCST) and high temperature (50 °C, T > LCST) conditions, due to the reduced compatibility of polymer chains in the aqueous solution, the polymer-rich phase showed aggregated and dense bright spots in the CLSM image. It is worth noting that the polymer phase size was significantly smaller and denser at high temperature, demonstrating that the two phase transitions originated from different mechanisms.

[0043] The cross-sectional morphological structure of Gel-H / C5 hydrogel at different temperatures was investigated by scanning electron microscopy (SEM). From attached Figure 3 b, it can be seen that Gel-H / C5 hydrogel呈现多孔网状结构。由于CMC和聚合物分子链之间形成缠结,Gel-H / C5的断面更粗糙。当水凝胶暴露于低温(2℃,T<UCST)时,可以观察到水凝胶的孔壁变厚,这归因于PAM和HPC分子链之间的氢键相互作用。而当水凝胶暴露于高温(50℃,T>LCST)下,显示出疏松的大孔蜂窝结构。而Gel-H / C5比Gel-H / C0孔壁更厚,这是由于CMC的加入使得Gel-H / C5的LCST相变温度降低,使HPC疏水聚集更加明显。

[0044] The microstructure of Gel-H / C5 hydrogel at different temperatures was further analyzed by in-situ small-angle X-ray scattering (SAXS). As attached 注:原文中“呈现多孔网状结构”处的中文表述有误,我按照正确理解翻译为“exhibits a porous network structure” 。另外,原文中一些符号(如 Figure 3 处的中文乱码)无法准确翻译其含义,所以保留原样。你可检查下原文内容是否准确完整,若有问题欢迎随时指出。 Figure 3 As shown in Figure c, the scattering intensity (I(q)) decreases with the increase of q, and there is almost no obvious characteristic peak, indicating that the internal structure of the hydrogel is uniform. It is worth noting that the scattering intensity of Gel-H / C5 is the weakest at 25°C, indicating that phase separation does not occur at this time. However, when cooled to 2°C, the scattering intensity becomes larger, which is due to the phase separation of the aggregation of polymer molecular chains. When heated to 40°C, the scattering intensity increases further, indicating that the hydrophobic aggregation of HPC molecular chains exhibits stronger light scattering. In addition, the radius of gyration (Rg) of Gel-H / C5 hydrogel at 25°C is 32.4nm, which is higher than the Rg at 2°C (30.6nm) and 40°C (27.7nm), indicating that phase separation makes the molecular chains tighter.

[0045] CMC forms entanglements with polymer molecular chains, which greatly enhances the mechanical properties of hydrogels. As the CMC content increases from 0wt% to 5wt%, the hydrogels show a significant increasing trend in both tensile stress and tensile strain (see Appendix Figure 3 d). When the CMC content reaches 5wt%, the tensile strength of Gel-H / C5 hydrogel is 54kPa, which is more than twice that of Gel-H / C0; at the same time, its elongation at break is 204%, which is almost three times that of Gel-H / C0 (see Appendix Figure 4 ). This phenomenon confirms that the topological entanglement formed by CMC, PAM and HPC molecular chains effectively improves the mechanical properties of the hydrogel. In addition, CMC, as a sodium salt, can improve the antifreeze ability of the hydrogel and ensure the stability and reliability of the hydrogel in low temperature environments. Figure 5 It shows that Gel-H / C5 hydrogel can be twisted and stretched arbitrarily without any damage after being refrigerated at -15℃ for 12h. Figure 3 e) It can be seen that the crystallization peak of Gel-H / C5 hydrogel is at -18 °C, which is 6 °C lower than the crystallization temperature of Gel-H / C0 (-12 °C), indicating that Na + The ions prevent water molecules from aggregating and forming ice crystals.

[0046] Example 4

[0047] Thermal insulation performance test of Gel-H / C gel at different temperatures

[0048] As we all know, thermal radiation in the near-infrared (IR, 780-2500am) region contributes 53% of the total solar energy (UV is 3%; visible 44%). Considering that Gel-H / C5 hydrogel maintains high transparency within the temperature range suitable for the human body, it can well meet the application requirements of smart windows. Therefore, the transmittance of Gel-H / C5 hydrogel at different temperatures in the range of 250-2500nm was tested. Figure 6 As shown in the figure, the transmittance of Gel-H / C5 hydrogel in the visible light range is less than 25% at 2°C, the transmittance is more than 90% at 25°C, and the transmittance of Gel-H / C5 hydrogel in the range of 250-2500nm is close to 0% at 40°C. It is worth noting that the transmittance of the hydrogel in the IR region drops sharply, indicating that Gel-H / C hydrogel has good IR blocking function, which is crucial for the thermal insulation and energy-saving performance of smart windows. The transmittance modulation efficiency of Gel-H / C5 hydrogel is calculated (Ttum=90.24%,ΔTsolar,25-2℃=66.88%,ΔTsolar,25-40℃=80.81%). The high Tlum of Gel-H / C5 ensures high indoor visibility during the day without additional lighting; while in cool nights and hot summers, the low transmittance can block indoor lights and infrared rays, which can protect privacy and heat insulation. In order to evaluate the reliability and durability of Gel-H / C5 hydrogel, 25 cycles of heating-cooling were carried out in the range of 2-40°C and the transmittance change at 550nm was tested. During the 25 cycles, the transmittance of Gel-H / C5 hydrogel at 2°C, 25°C and 40°C hardly changed, showing a reversible and stable phase change, which ensured a good service life in the application.

[0049] In order to demonstrate the application potential of Gel-H / C5 hydrogel as a smart window in terms of thermal insulation performance, a hydrogel sample with a thickness of 1 mm was assembled into a simulated house model (see Appendix). Figure 7 At the same time, a model house with ordinary glass windows was assembled for comparison. In the initial state, the temperature in both model houses was about 28.4℃. At this time, the smart window was in a transparent state, and the scenery outside the window could be clearly seen (see attached). Figure 7 a). After 4 hours of sunshine, as the ambient temperature began to rise, the smart window turned into an opaque state. The indoor temperature monitoring results of the model room showed that the temperature of the model room with ordinary glass windows reached 52.4℃, while the temperature of the model room with smart windows was only 49.0℃, which was about 3.4℃ lower than that of the model room with ordinary glass windows (see Appendix Figure 7b). These experimental results confirm that compared with traditional glass windows, the Gel-H / C5 smart window can not only effectively adjust the light transmittance and reduce direct sunlight, but also adjust the indoor temperature, showing good heat insulation and energy saving effects.

[0050] Example 5

[0051] Dual thermal responsiveness and controllable dynamic visual changes based on Gel-H / C gel

[0052] Based on the dual thermal response ability and controllable dynamic visual changes of Gel-H / C gel, its application potential in QR code information encryption and decryption was designed and demonstrated. Figure 8 As shown, firstly, the strip-shaped Gel-H / C0, Gel-H / C2 and Gel-H / C5 gels are placed in order and then sealed in a glass interlayer with silica gel. Then the device is placed on top of the QR code paper, with black cardboard as the background, to form a QR code information encryption device. Figure 8 a It can be seen that since the three gels are opaque at 1°C, the QR code information is invisible and is in an encrypted state. When the temperature rises to 15°C, the QR code information hidden by Gel-H / C5 is revealed, but the complete information cannot be obtained at this time. When the temperature reaches 25°C, all gels become transparent, and the QR code information is completely decrypted. By scanning the QR code, the hidden information (a landscape photo) can be obtained. When the device is then heated to 35°C again, the Gel-H / C5 and Gel-H / C2 gels undergo LCST phase transitions and become opaque, and the QR code information is hidden again. When the temperature rises to 50°C, the QR code information is in a completely encrypted state.

[0053] In addition, a pattern information encryption device is designed. Figure 8 As shown in Figure b, the heart-shaped Gel-H / C5 gel is embedded in Gel-H / C0 (1 mm thick) and encapsulated in a glass interlayer with silicone. When photographed with a black cardboard as the background, the device becomes opaque as a whole at 1°C, and the pattern information is completely hidden. As the temperature rises to 15°C, the heart-shaped pattern is completely decrypted; and when the temperature rises to 25°C, Gel-H / C0 also becomes transparent, the heart-shaped pattern disappears, and the pattern is in an encrypted state. As the temperature further rises to 35°C, the pattern information is decrypted again in an opaque state; when the temperature reaches 50°C, the device becomes opaque again as a whole, and the pattern information is completely encrypted again. This process can be repeated many times without any change in appearance.

Claims

1. A method for preparing a cellulose-based hydrogel with dual temperature stimulus response, characterized in that: The method comprises the following steps: first, dissolving hydroxypropyl cellulose (HPC) and acrylamide (AM) in deionized water; then, adding appropriate amounts of sodium carboxymethyl cellulose CMC, crosslinking agent N,N'-methylenebisacrylamide (MBA) and initiator ammonium persulfate (APS), stirring until completely dissolved and then centrifuging to remove bubbles; finally, injecting the prepared precursor solution into a sealed mold and reacting at high temperature to obtain the final dual temperature stimulus responsive cellulose-based hydrogel Gel-H / C.

2. The method for preparing a dual temperature stimulus responsive cellulose-based hydrogel according to claim 1, characterized in that: When hydroxypropyl cellulose (HPC) and acrylamide (AM) are dissolved in deionized water, the mass percentage concentration of hydroxypropyl cellulose (HPC) is 5 wt %, and the mass percentage concentration of acrylamide (AM) is 2 mol / L.

3. The method for preparing a dual temperature stimulus responsive cellulose-based hydrogel according to claim 1, characterized in that: Add appropriate amounts of sodium carboxymethyl cellulose (CMC), crosslinking agent N,N'-methylenebisacrylamide (MBA) and initiator ammonium persulfate (APS), stir until completely dissolved and then centrifuge to remove bubbles, and the mass percentage concentration of sodium carboxymethyl cellulose (CMC) is 0wt% to 5wt%.

4. The method for preparing a dual temperature stimulus responsive cellulose-based hydrogel according to claim 1, characterized in that: The prepared precursor solution is injected into the mold, sealed and reacted at high temperature to obtain the final dual temperature stimulus responsive cellulose-based hydrogel Gel-H / C. The reaction temperature is 60°C and the reaction time is 6 hours.

5. The dual temperature-responsive cellulose-based hydrogel of claim 1 can achieve reversible switching of transparency in the range of 1°C to 50°C as the ambient temperature changes.

6. Use of the dual temperature stimulus responsive cellulose-based hydrogel according to claim 1 in anti-counterfeiting materials.

Citation Information

Patent Citations

  • Preparation of rapid swelling aquogel

    CN101177488A

  • Thermochromic composite material for intelligent window

    CN113773599A

  • Preparation method of gelatin-based thermochromic hydrogel material

    CN117209692A

  • Preparation method and application of cellulose-based temperature and pressure dual-response type conductive hydrogel

    CN117467082A

  • Thermostable, printable and LCST-adjustable thermochromic gel, preparation method thereof and thermochromic gel coating

    CN118702866A